MRI evaluation of cranial pathologies in rapidly progressive early puberty cases aged 8-9 - Kılınç Uğurlu, Aylin; Özdemir Gökce, Ayse; Çakır Gündoğan, Seçil; Ekşioğlu, Ayşe Seçil; Boyraz, Mehmet (Frontiers in Endocrinology, 2024)
The aim of this study was to investigate the frequency and distribution of intracranial pathologies in female patients between 8 and 9 years of age who were diagnosed with early puberty (rapidly progressive) through the evaluation of MRI images.: A total of 74 female patients diagnosed with central precocious puberty (CPP) (6-8 years) and rapidly progressive early puberty (RPEP) (8-9 years) were included in the study. The patients were categorized into two groups, normal and abnormal, based on the findings from their MRI scans. Recent literature has classified abnormal MRI findings into three groups: pathological findings, findings with a questionable relationship to CPP, and incidental findings. Furthermore, the patients were divided into four groups based on their MRI findings and whether they had CPP or RPEP:CPP (6-8 years) +Normal MRI, RPEP (8-9 years) + Normal MRI, CPP (6-8 years) +Abnormal MRI, RPEP (8-9 years) +Abnormal MRI.Results: Out of the 74 girls included in the study, 54% (n=40) showed normal MRI results, while abnormal MRI findings were detected in 46% (n = 34) of the cases. No malignant lesions were identified among cases with abnormal MRI findings. The occurrence of abnormal MRI findings was observed in 46% of the PP group and 45% of the RPEP group. Incidental findings were the most common MRI findings in both groups. The proportion of cases with pathological findings and findings with a questionable relationship to CPP was similar in both groups (p = 0.06). Basal luteinizing hormone (LH) concentration was found to be higher in the RPEP (8-9 years) +Abnormal MRI group compared to the CPP (6-8 years) +Normal MRI group (p = 0.01).Our study is the first to investigate MRI findings in cases of rapidly progressive early puberty in the age range of 8-9 years. Our study demonstrates that there is no difference in terms of intracranial findings between cases of precocious puberty at the age of 6-8 years and cases of rapidly progressive early puberty aged 8-9.Notably, an exaggerated LH response may serve as a potential indicator for pathological findings on MRI in cases of rapidly progressive early puberty.